Selective laser melting of aluminium alloys - Aboulkhair, Nesma T.; Everitt, Nicola M.; Maskery, Ian; Ashcroft, Ian; Tuck, Chris (Cambridge University Press, 2017)
Metal additive manufacturing (AM) processes, such as selective laser melting, enable powdered metals to be formed into arbitrary 3D shapes. For aluminium alloys, which are desirable in many high-value applications for their low density and good mechanical performance, selective laser melting is regarded as challenging due to the difficulties in laser melting aluminium powders. However, a number of studies in recent years have demonstrated successful aluminium processing, and have gone on to explore its potential for use in advanced, AM componentry. In addition to enabling the fabrication of highly complex structures, selective laser melting produces parts with characteristically fine microstructures that yield distinct mechanical properties. Research is rapidly progressing in this field, with promising results opening up a range of possible applications across scientific and industrial sectors. This paper reports on recent developments in this area of research as well as highlighting some key topics that require further attention.